Patērētāju uzvedības salīdzinājums nedzīvības apdrošināšanas tirgū Latvijā un Krievijā - Karabanina, Anna (Latvijas Universitāte, 2013)
The topic of Master thesis is “The comparison of consumer behavior on non-life insurance market in Latvia and Russia”. The aim of the Master thesis is to compare the consumer behavior on non – life insurance markets in Latvia and in the Russian Federation, to find out main distinctions among these countries. Nowadays, an insurance company has become a universal way of protection of interests of individuals and legal entities, that’s why the insurance company has to be flexible to any change on the market. But this is impossible without study of consumer behavior. In the research, the author has focused on two types of factors, which have impact on consumer behavior on an insurance market: personal characteristics of consumers and factors related to marketing activity of an insurance company. The author has worked out the research, using the survey. The survey was conducted from February 2013 till April 2013. The respondents from Latvia and Russia took part in the survey.

Maģistra darba tēma ir „Patērētāju uzvedības salīdzinājums nedzīvības apdrošināšanas tirgū Latvijā un Krievijā”. Maģistra darba mērķis ir salīdzināt patērētāju uzvedību nedzīvības apdrošināšanas tirgū Latvijā un Krievijas Federācijā, lai konstatētu galvenās atšķirības šo valstu starpā. Mūsdienās apdrošināšanas sabiedrība kļuvusi par universālu privātpersonu un juridisku personu interešu aizsardzības veidu, tāpēc tai jābūt fleksiblai attiecībā pret jebkurām tirgus izmaiņām. Bet tas nav iespējams bez patērētāju uzvedības izpētes. Autora pētījuma uzmanības centrā ir divi tādu faktoru veidi, kas ietekmē patērētāju uzvedību apdrošināšanas tirgū: patērētāju personības īpašības un faktori, kas saistīti ar apdrošināšanas sabiedrības tirgus aktivitātēm. Autors pētījuma veikšanai izmantoja anketēšanu. Tā tika veikta no 2013. gada februāra līdz 2013. gada aprīlim. Anketēšanā piedalījās respondenti no Latvijas un Krievijas.
The comparision of consumer behavior on non-life insurance markets in Latvia and Russia
Keywords: Ekonomika